The affinity and selectivity of α‐adrenoceptor antagonists, antidepressants, and antipsychotics for the human α1A, α1B, and α1D‐adrenoceptors - Richard G. W. Proudman; Andre S. Pupo; Jillian G. Baker (Wiley, 2020)
Abstract α1‐adrenoceptor antagonists are widely used for hypertension (eg, doxazosin) and benign prostatic hypertrophy (BPH, eg, tamsulosin). Some antidepressants and antipsychotics have been reported to have α1 affinity. This study examined 101 clinical drugs and laboratory compounds to build a comprehensive understanding of α1‐adrenoceptor subtype affinity and selectivity. [3H]prazosin whole‐cell binding was conducted in CHO cells stably expressing either the full‐length human α1A, α1B, or α1D‐adrenoceptor. As expected, doxazosin was a high‐affinity nonselective α1‐antagonist although other compounds (eg, cyclazosin, 3‐MPPI, and ARC239) had higher affinities. Several highly α1A‐selective antagonists were confirmed (SNAP5089 had over 1700‐fold α1A selectivity). Despite all compounds demonstrating α1 affinity, only BMY7378 had α1D selectivity and no α1B‐selective compounds were identified. Phenoxybenzamine (used in pheochromocytoma) and dibenamine had two‐component‐binding inhibition curves at all three receptors. Incubation with sodium thiosulfate abolished the high‐affinity component suggesting this part is receptor mediated. Drugs used for hypertension and BPH had very similar α1A/α1B/α1D‐adrenoceptor pharmacological profiles. Selective serotonin reuptake inhibitors (antidepressants) had poor α1‐adrenoceptor affinity. Several tricyclic antidepressants (eg, amitriptyline) and antipsychotics (eg, chlorpromazine and risperidone) had high α1‐adrenoceptor affinities, similar to, or higher than, α blockers prescribed for hypertension and BPH, whereas others had poor α1 affinity (eg, protriptyline, sulpiride, amisulpiride, and olanzapine). The addition of α blockers for the management of hypertension or BPH in people already taking tricyclic antidepressants and certain antipsychotics may not be beneficial. Awareness of the α‐blocking potential of different antipsychotics may affect the choice of drug for those with delirium where additional hypotension (eg, in sepsis) may be detrimental.